Gastrostomy Plus Fundoplication or Gastro-Jejunal Tube Versus Gastrostomy Alone for Gastro-Esophageal Reflux in Children with Neurological Impairment - Campos-Varas, J (John Wiley and Sons Ltd, 2022)
Objectives: This is a protocol for a Cochrane Review (intervention). The objectives are as follows:. To assess the benefits and harms of the two most common enteral feeding tubes and associated antireflux procedures. We aim to compare: (1) gastrostomy plus fundoplication and (2) gastrostomy plus insertion of a GJ tube, versus gastrostomy alone for children with NI. Copyright © 2022 The Cochrane Collaboration. Published by John Wiley & Sons, Ltd.